Prioritizing Acculturative Stressors Impacting Family Cohesion: A Mixed-Methods Analysis Among Immigrant Families in Argentina - El Amrani, Aleksandra; Barrenechea, Nicolás; Torres, Camila (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to identify, categorize, and prioritize the key acculturative stressors that most significantly impact family cohesion among immigrant families residing in Argentina. Methods and Materials: A sequential exploratory mixed-method design was employed, integrating qualitative and quantitative phases. In the qualitative phase, a comprehensive literature review was conducted until theoretical saturation was reached, and data were analyzed using NVivo 14 to extract themes and subthemes related to acculturative stress and family functioning. Seven main categories were identified: intergenerational value conflict, marital and family role strain, economic and occupational pressure, discrimination and social exclusion, cultural identity negotiation, community and social support deficiency, and language and communication barriers. In the quantitative phase, a structured questionnaire based on these categories was administered to 195 immigrant participants in Argentina. Responses were analyzed using SPSS version 26, applying descriptive statistics and the Friedman test to determine mean ranks of the stressor categories. Findings: The Friedman test revealed significant differences among the perceived impact levels of the seven acculturative stressor categories (χ² = 64.27, p < 0.001). Intergenerational value conflict ranked highest (Mean Rank = 6.78), followed by marital and family role strain (Mean Rank = 6.12) and economic and occupational pressure (Mean Rank = 5.86). The lowest-ranked stressors were community and social support deficiency (Mean Rank = 4.37) and language and communication barriers (Mean Rank = 3.72). These results indicate that internal, relational stressors exert greater influence on family cohesion than external or structural factors. Conclusion: The findings underscore that intrafamilial stressors—particularly intergenerational and role-related conflicts—pose the most critical threats to family cohesion in immigrant households. Strengthening intergenerational communication, enhancing marital adaptability, and fostering culturally responsive support systems are vital for promoting resilience and cohesion in acculturating families.